2010
DOI: 10.1073/pnas.1002130107
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide adenine dinucleotide (NAD)–regulated DNA methylation alters CCCTC-binding factor (CTCF)/cohesin binding and transcription at the BDNF locus

Abstract: Cellular metabolism alters patterns of gene expression through a variety of mechanisms, including alterations in histone modifications and transcription factor activity. Nicotinamide adenine dinucleotide (NAD)-dependent proteins such as poly(ADP ribose) polymerases (PARPs) and sirtuin deacetylases play important roles in this regulation, thus NAD provides a crucial link between metabolism and these cellular signaling processes. Here, we found that lowering NAD levels in mouse primary cortical neurons led to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…It is possible that in our system, BDNF maintains the NAD level in the neurons; however the mechanism is not the same for the maintenance of the NAD level in activated infiltrated cells. Interestingly Chang et al, 2010 recently reported that the NAD levels modulate BDNF expression (Chang et al, 2010). Together our results are consistent with the hypothesis that BDNF may reduce the severity of EAE by preventing the depletion of NAD levels in inflammation and protecting neuronal cells.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that in our system, BDNF maintains the NAD level in the neurons; however the mechanism is not the same for the maintenance of the NAD level in activated infiltrated cells. Interestingly Chang et al, 2010 recently reported that the NAD levels modulate BDNF expression (Chang et al, 2010). Together our results are consistent with the hypothesis that BDNF may reduce the severity of EAE by preventing the depletion of NAD levels in inflammation and protecting neuronal cells.…”
Section: Discussionsupporting
confidence: 91%
“…However, NAMPT is highly expressed in several cancers, and features of cancer cells, including proliferation, invasion, and tumor growth, exhibit a dependence on NAD + (9)(10)(11). In noncancer cells, NAD + plays a critical role in transcriptional control, providing a metabolic basis for epigenetic reprogramming (12)(13)(14)(15)(16). Enzymes using NAD + as a cofactor, including the sirtuins and poly-ADP ribosyl transferases, regulate transcription factor activity and chromatin structure (13)(14)(15).…”
mentioning
confidence: 99%
“…Enzymes using NAD + as a cofactor, including the sirtuins and poly-ADP ribosyl transferases, regulate transcription factor activity and chromatin structure (13)(14)(15). Additionally, NAD + can control transcription by altering DNA methylation in neurons (12). However, in glioblastoma, little is known about NAD + -dependent transcriptional events and whether these events impact malignant behavior and therapy response.…”
mentioning
confidence: 99%
“…This structural restriction of silenced chromatin on gene expression can be overcome by chromatin writer, reader, and eraser enzyme complexes, which remodel nucleosomes along the DNA or reversibly modify (acetylation, phosphorylation, ubiquitylation, glycosylation, and sumoylation) histones on lysine, arginine, serine, or threonine residues of amino-terminal histone tails and establish specific chromatin states involved in transcription [20][21][22]. One critical facet of histone and DNA modifying enzymes is that their activity also depends on intracellular levels of essential metabolites [acetyl-coA, Fe, ketoglutarate, nicotinamide adenine dinucleotide (NAD) + , and SAM], the concentrations of which are tightly linked to global cellular metabolism and energy levels [23][24][25][26][27][28][29]. Gene regulation is thus linked to the metabolic status of cells ( Fig.…”
Section: Introductionmentioning
confidence: 99%